724 STAT3 inhibition in acute myeloid leukemia cells allows for TLR9-driven differentiation to immunogenic monocytic cells and induction of T-cell mediated immune responses. (9th November 2020) - Su, Yu-Lin; Kortylewski, Marcin; Duttagupta, Priyanka
Abstract : Background: Signal transducer and activator of transcription factor 3 (STAT3) is commonly activated in acute myeloid leukemia (AML) and known for supporting cancer cell proliferation and survival. Recently, we demonstrated that STAT3 also plays a critical role ensuring AML immune evasion. Intravenous injections of bi-functional decoy oligodeoxyribonucleotides (CpG-STAT3dODN) blocked STAT3 activity and induced TLR9 signaling in Cbfb/MYH11/Mpl (CMM) AML cells, thereby resulting in immunogenic effects and T cell-mediated immune responses and leukemia regression. Methods: To understand the molecular mechanisms of the CpG-STAT3 decoy-induced AML differentiation and immunogenicity, we performed global gene expression analysis on the in vivo treated AML cells using oligonucleotide strategy as well as an inducible STAT3 gene silencing. Results: Transcriptional profiling revealed the upregulation of myeloid cell differentiation related genes, such as Irf8, Cebpa, and Gadd45A with reduction of oncogenic Runx1 and Run1t1 in CMM leukemic cells after CpG-STAT3dODN but not after control treatments. CpG-STAT3dODN treatment also upregulated set of antigen-presentation related genes, such as CIIta, Il12a, and Ifng in CMM AML cells. Importantly, the induction of Irf8 and Cebpa, with the concomitant suppression of Runx1 were found specifically in the subset of differentiated CD11b+ CMM cells but not in the bulk CD11b– leukemic cells. These effects were likely related to epigenetic reprogramming of AML cells as indicated by treatment-induced changes in the expression and protein levels of STAT3 regulated DNA methyltransferases, DNMT1 and DNMT3a/b. Furthermore, our initial studies suggest that STAT3 inhibition/TLR9 activation leads to immunogenic effects also in a xenotransplanted model of human FLT3-ITD MV4-11 leukemia in humanized mice. CpG-STAT3dODN alone or together with clinically-relevant demethylating agent (Decitabine) triggered differentiation of MV4-11 cells into CD11b+HLA-DR+CD86+ antigen-presenting cells (APCs) and increased ratio of CD8+ to regulatory T cells in the bone marrow, thereby reducing leukemia burden. Conclusions: Our results suggest that eliminating STAT3 permits the TLR9-driven reprogramming of AML cells into APCs to unleash T cell-mediated responses against leukemia.